Jewish and Arab childhood in Israel: contemporary perspectives - Barʿam Eshel, ʿEnat; Jayusi, Wurud; Paul-Binyamin, Ilana; Younis, Eman (Lexington Books, 2021)
In this edited collection on Jewish and Arab childhood in Israel, contributors illuminate the experiences of the individual child with family and community, the formal education system, and informal leisure culture, and they explore representations of childhood and its perceptions in literature and culture.